Characterization and pathogenicity of Pantoea stewartii subspecies stewartii causing bronzing disease of jackfruit (Artocarpus heterophyllus lam.) in Peninsular Malaysia - Abidin, Nuraizat (2020)
Jackfruit (Artocarpus heterophyllus Lam.) is one of the most popular fruit. In Malaysia, it is important to keep the fruit healthy as it provides revenue to the local and export markets and enhancing economic contribution towards the gross domestic product (GDP) in Malaysia. However, a disease known as jackfruit-bronzing is frequently found in the jackfruit crop. The reddish discolouration, and rusty specks or bronzing with yellowish-orange discolouration symptoms affected pulps and rags of the fruit. Jackfruit-bronzing is suspected to be caused by Pantoea stewartii subspecies stewartii (P. stewartii subsp. stewartii). The objectives of the study were (i) To identify the bacterial strains associated with bronzing disease of jackfruit in Peninsular Malaysia using phenotypic and molecular characteristics; (ii) To determine the pathogenicity of P. stewartii subsp. stewartii on jackfruits and host range of P. stewartii subsp. stewartii on sweetcorn, cucumber and pineapple and (iii) To assess and determine the genetic diversity of P. stewartii subsp. stewartii strains associated with bronzing disease of jackfruit using multilocus sequence analysis (MLSA). Twenty-eight pure bacterial isolates obtained from samples with typical jackfruit-bronzing symptoms from four different collection area in Peninsular Malaysia, comprises of Jenderam from Selangor state, Maran and Muadzam Shah from Pahang state and Ipoh from Perak state) were studied. Phenotypic verification, molecular verification, pathogenicity test on different jackfruit varieties, host range test on sweetcorn, cucumber and pineapple as well as the genetic diversity were performed in this study. Phenotypic characterization revealed positive P. stewartii subsp. stewartii verification based on the eleven phenotypic tests and hypersensitivity test. Molecular characterization performed via the 16S-23S Internally Transcribed Spacer (ITS) yielded the expected amplicons (0.92-kb fragment). Phylogenetic analyses confirmed that all of the 28 bacterial strains of P. stewartii subsp. stewartii were clustered to reference strains of Stewart’s wilt causing disease in the USA (DC283) and jackfruit-bronzing strains studied earlier in Malaysia (S3 and W1). Pathogenicity tests on jackfruit varieties all produced symptoms thus fulfilling Koch’s postulate, except for jackfruit variety J39 (no symptom was observed). Furthermore, the host range testing on sweetcorn (nine-week-old seedlings), cucumber and pineapple also produced symptoms. A significant difference (p < 0.05) in the disease severity was exhibited by jackfruit varieties J33, J34 and J39. Statistical analyses based on pathogenicity tests on jackfruits and host range test on sweetcorn, pineapple and cucumber (period of 14 days) on its collection area showed consistency with significant difference (p < 0.05) for the strains collected, where Jenderam showed the highest disease severity (%) among all the strains, except in the host range test on cucumber. There was also consistency with significant difference (p < 0.05) for the strains collected from Jenderam and Maran with the strains collected from Muadzam Shah and Ipoh (period of 14 days). The total disease rating on the jackfruit varieties, sweetcorn, cucumber and pineapple on day 14 revealed that the JEN-14 strain demonstrated the highest severity or aggressiveness. Multilocus sequence analysis (MLSA) was performed using four housekeeping genes (gyrB, rpoB, atpD and infB) on the 28 bacterial strains. Single gyrB, rpoB, atpD and infB and concatenated genes phylogenetic trees of this study showed the bootstrap value of 99-100% between the 28 bacterial strains with P. stewartii subsp. stewartii reference strains and P. stewartii subsp. indologenes reference strains. Moreover, the phylogenetic analysis based on the concatenated genes were able to distinguish that the strains were more closely related to P. stewartii subsp. stewartii (99 similarities) from its close relative P. stewartii subsp. indologenes, although sequence similarity between the subspecies was high (up to 100%). All the strains collected from the four collection areas clustered together, showing no variation between the collection area of the bacterial strains. These findings point no correlation between the disease severity and MLSA’s genetic cluster of the 28 bacterial strains. This study would be a major platform on generating details documentation on bronzing disease of jackfruit and its causal pathogen, P. stewartii subsp. stewartii in Malaysia, since jackfruit has been identified as one of the most important commercial fruit crops with high economic value in this country.